Advance cryptography algorithm for improving data security - SINGH, YASHWANT KUMAR; Milan, Ram; RATAWA, SURYA PRAKASH (IJRDO -Journal of Computer Science Engineering, 2017)
Information security is the process of protecting information. It protects its availability, privacy and integrity. Access to stored information on computer databases has increased greatly. More companies store business and individual information on computer than ever before. Much of the information stored is highly confidential and not for public viewing. In this paper, I have developed a new cryptography algorithm, which is based on block cipher concept. In this algorithm, I have used logical operation like XOR and shifting operation. Experimental results show that proposed algorithm is very efficient and secured. To write this paper I have Study about information security using cryptography technique. After the detailed study of Network security using cryptography, I am presenting my proposed work. This paper is dividing in four sections. In section-I, I am presenting just basic introduction about Information Security using cryptography, in section-II, I am presenting detailed description of Information security using cryptography and various algorithms, in section-III, I am presenting my proposed algorithm, and in section IV I am Presenting summary and references where I have completed my research. The proposed algorithm has the batter speed compared with the comparing encryption algorithm. Nevertheless, the proposed algorithm improves encryption security by inserting the symmetric layer. The proposed algorithm will be useful to the applications, which require the same procedure of encryption and decryption.